Da macropolítica às contradições e desafios em nível local : descortinando o PROEJA FIC em Passo Fundo/RS - Xavier, Ângela (2013)
This research aimed to investigate how was the experience of the National Program for the Integration of Professional Education with Basic Education in the Modality of Education of Youths and Adults, Initial Formation and Continuing with School (PROEJA FIC) in the city of Passo Fundo, Rio Grande do Sul (RS), as an interface between the macro and microcontext, implemented at the local level in the period from 2010 to 2011, through a partnership between the Federal Institute of Education, Science and Technology of Rio Grande do Sul (IFSul), Campus Passo Fundo, and the Municipal Education this city related to Education of Youths and Adults (EJA). In theoretical contributions were sought of Sérgio Haddad, Maria Clara Di Pierro, José Gimeno Sacristán, Angel Perez I. Gómez, Dermeval Saviani, Gaudêncio Frigotto, Maria Ciavatta, Marise Ramos, Acácia Kuenzer, Jane Paiva, Maria Margarida Machado, Miguel Arroyo, among others. Methodologically, the research was configured as a case study, qualitative approach with a quantitative dialogue, involving the use of questionnaires with teachers who worked in the local process, conducting structured interviews with program graduates and analysis of official documents. The dissertation is structured in five chapters. The first is the introduction which presents the issues involved in building research; shows the delimitation of the subject, the justification, the look of the researchers on the topic, the research question, the objectives, a summary of the methodological options, and the structure that supported this research. The second chapter analyzed the history of adult education in Brazil since 1990, indicating the main socio-historical developments and legal consequences that brought the EJA, emphasizes the tradition of programs for adult education and workers, making a synthesis of same; historicizes Professional Education Reform 1996, regulated by Decree 2.208/1997 and their inheritance to the EJA. The third chapter features PROEJA FIC nationwide, covering their genesis, translated by trajectory from its inception, through the decrees, and its document base; presents his conception of comprehensive training and dialogue and polytechnic omnilateral according with its guiding documents, portrayed from its assumptions and principles; also discusses how to operationalize the program as a whole and ends with its implementation at the national level. The fourth chapter focuses on the methodological approach adopted, portraying the empirical space, consisting of the site and the research subjects; presents the instruments and procedures used in data collection; describes the course in Construction idealized based on the guidelines macropolitics PROEJA FIC deployed in Passo Fundo. The fifth and final chapter presents the analysis and interpretation of data, seeking answers to the main question, from the documents and the look of the study subjects. According to the data analysis, identifies the complexity and contradictions between the macro and the microcontext PROEJA FIC, ranging from the deployment, implementation until the results of the program. In this process, it is emphasized the final findings of the research, on the one hand, developments and reflections promoted in the local context because: (a) the phenomenon of younger players, (b) the permanence of the historical split between education and work, (c) the prevalence of structural duality and, (d) the high dropout rate. On the other hand, there is the intention of macropolitics in promoting social inclusion emancipatory in contrast to the other proposals in the Brazilian educational scenario implemented in this framework